Comparative Analysis of Hadejia and Guddiri Dialects of Hausa (British Journal of Multidisciplinary and Advanced Studies, 2024)
It is a common phenomenon in any society to have a different group of people who speak the same language based on their regional or social identity, but one may find that, there are some similarities and differences among the languages ​​of these groups. These differences are called variation. The particular variation which is peculiar to a specific region or social group is called dialect (Wardhaugh & Fuller, 2015). The Hausa language is one of the languages ​​that is full of different dialects. Those include Kananci (Kano dialect), Sakkwatanci (Sokoto dialect), Guddiranci (Guddiri dialect), Haɗejanci (Haɗejia dialect) and so on. This dynamism of language as a means of communication is what makes it an area worthy of research. The Haɗejia and Guddiri dialects are said to be the same by some researchers. Thus, this study aims to examine the differences and similarities between Haɗejia and Guddiri dialects.